1979
DOI: 10.2190/54n9-6a3p-l4eq-vtp6
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Requests, Initial Sessions and Attrition

Abstract: Treatment attrition in a psychiatric outpatient department was evaluated. Of eighty-two consecutive new patients, fifty-three (65%) showed up for a second appointment while twenty-nine (35%) failed to return. None of the demographic variables or specific categories of patient requests differentiated continuers from non-continuers; nor was attrition significantly influenced by feeling one's problems were understood, symptomatic improvement or receiving the kind of intervention originally desired. Treatment cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…When a patient enters the initial interview with specific treatment requests which are ignored, this may interfere with future adherence to treatment recommendations (Eisenthal et al 1979;Eisenthal, Koopman & Lazare, 1983). However, thus far, the limited research attempting to determine whether understanding patients' requests (or other factors of the &dquo;negotiated approach&dquo;) leads to improved adherence to treatment has produced mixed findings (Eisenthal et al 1979;Zisook al. 1979b) and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a patient enters the initial interview with specific treatment requests which are ignored, this may interfere with future adherence to treatment recommendations (Eisenthal et al 1979;Eisenthal, Koopman & Lazare, 1983). However, thus far, the limited research attempting to determine whether understanding patients' requests (or other factors of the &dquo;negotiated approach&dquo;) leads to improved adherence to treatment has produced mixed findings (Eisenthal et al 1979;Zisook al. 1979b) and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…1979;Eisenthal, Koopman & Lazare, 1983;Hornstra, Lubin & Lewis, 1972;Tracey, 19~6), but at this time, this is not clearly demonstrated by the available research (Zisook al. 1979b).…”
Section: Introductionmentioning
confidence: 87%
“…Dissatisfaction with services or therapists is frequently mentioned by UTs as their reason for quitting (Acosta, 1980; DuBrin & Zastowny, 1988; Gill, Singh, & Sharma, 1990; Pekarik, 1983b, 1992). UTs’ levels of satisfaction with therapy or therapist tend to be significantly lower than are continuers’ or completers’ (McNeill, May, & Lee, 1987; Papach-Goodsitt, 1986; Zisook, Hammond, Jaffe, & Gammon, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…14 In contrast to the multitude of studies characterizing patient factors resulting in missed appointments, there are few studies evaluating how NSs are viewed and managed by the primary care team. [15][16][17][18] Although data are limited, survey and focus group data of primary practices suggested that patient factors were perceived as the main determinant for visit non-compliance as opposed to any practice factors. 17 Such attitudes by health care teams may correlate with design of interventions that implement consequences for NSs (penalty or fine) rather than implementing changes at a practice level.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some patients who were not seen may have reasonable justifications especially if they believed the visit was unnecessary or were dissatisfied with a previous encounter. 16 Regardless, greater patient communication, even if as simple as visit reminders, leads to fewer NSs compared to no communication. 18 To this end, by providing NS notification, the referring physician may play a critical role in investigating the NS, reassessing the need for the referral, and/or helping to eliminate barriers to keeping the visit.…”
Section: Discussionmentioning
confidence: 99%